Incident investigators' perspectives of incident investigations conducted in the Ghanaian mining industry. (February 2019) - Stemn, Eric; Hassall, Maureen E.; Cliff, David; Bofinger, Carmel
Highlights: Investigators had limited knowledge of causation models and investigation methods. Some investigators lack formal training although they continue to investigate. Post-investigation findings were often underutilised to improve the work process. There are different levels of maturity related to incident investigations. Abstract: Incident investigation has been regarded as one of the means of improving safety performance. Limited published research exists that focuses on the context of practical investigation and the perspectives of investigators in the field. This research addresses this gap by evaluating how investigations are conducted in the Ghanaian Mining Industry. Forty-one investigators with diverse backgrounds were interviewed and the data collected was analysed through qualitative content analysis. Results of the study indicate that the blame culture is still evident, there is a lack of focus on controls and narrow dissemination of post-investigation findings. 49% of investigators had no knowledge of accident causation models and investigation methods. 37% of investigators had received no investigation training although they continue to investigate incidents. The frequently used data sources included interviewing victims/witnesses and evidence from the incident scene, while data from safety-related activities such as previous investigations and risk assessment were often under-utilised. An event tree showing opportunities to improve incident investigation and learning was developed to support the prioritisation of strategies for improving investigation practices. A framework has also been proposed to help incident investigators self-assess the maturity/effectiveness of their investigation practices.